Antimicrobial activity of bacteriocins produced by lactic acid bacteria derived from Indonesian traditional fermented animal products: A review - Hidayatulloh, Akhmad; Rukayadi, Yaya; Putranto, Wendry Setiyadi; Suryaningsih, Lilis (Journal of Advanced Veterinary Research, 2026)
Bacteriocins produced by LAB isolated from traditional Indonesian fermented foods like dadih, urutan, bekasam, cangkuk, and bekamal show promising antimicrobial activity against pathogenic and spoilage bacteria. These bacteriocins are effective at inhibiting bacterial growth and maintaining food quality. The review discusses the isolation and characterization of LAB from these fermented products, the properties of the bacteriocins they produce, and their potential applications in food preservation. Bacteriocins from food-grade LAB are considered ideal biopreservatives due to their non-toxic nature, stability under various conditions, and effectiveness at low concentrations. The paper highlights the diversity of LAB strains found in traditional fermented foods and their ability to produce bacteriocins with broad-spectrum antimicrobial activity. Overall, this review emphasizes the potential of bacteriocins from indigenous fermented foods as natural antimicrobial agents for enhancing food safety and quality, aligning with consumer demand for minimally processed foods. Further research is suggested to optimize the production and application of these bacteriocins in food systems.